Colombia – Financial Sector Assessment : The Role of the State in the Provision of Financial Services - World Bank (Washington, DC: World Bank, 2022)
The State plays an important role in the provision of financial services in Colombia through state-owned financial institutions (SOFIs), interest rate controls, mandatory investment requirements and credit subsidies. State-owned financial institutions (SOFIs) hold about 12 percent of banking sector assets and about 8 percent of insurance sector assets. SOFIs are key actors in microcredit, agricultural and small business loans markets. The recently created Grupo Bicentenario (GB), a financial holding for SOFIs reporting to the Ministry of Finance (Ministerio de Hacienda y Credito Publico, MHCP), aspires to become the third largest financial group in Colombia. There are also fourteen small subnational development financial institutions (Institutos Financieros de Fomento y Desarrollo Territorial, INFIs), albeit the size of the sector is unknown as most INFIs do not disclose financials. All credit in Colombia is subject to interest rate controls, either ceilings under usury caps set relative to industry rates or regulated rates in socially sensitive sectors. Mandatory investments remunerated at below market rates are used to provide subsidized credit to the agricultural sector. The State also provides interest rate subsidies to private intermediaries lending to certain sectors and subsides agricultural insurance premiums. In the past, agricultural producers have received debt relief, undermining credit culture. Monitoring and evaluation (M and E) and disclosure of public credit support policies and programs and their costs should be substantially strengthened to assess value for money. Information on credit support programs and their subsidies should be systemically compiled, aggregated, and reported. Profitability of SOFIs excluding subsidies should be calculated and disclosed. A strategy for systematic and rigorous impact evaluation of public credit programs and policies should be designed and implemented. The GB should also formulate a strategy for the M and E function at the group level following international best practices that would facilitate aggregate monitoring and disclosing of SOFI activities.